A new method for improving the stability of high temperature piezoelectric properties in BiFeO3–BaTiO3 ceramics by regulating the relaxor transition. (1st October 2022) - Tan, Yunchuan; Zhou, Changrong; Wang, Jiang; Su, Di; Yuan, Changlai; Xu, Jiwen; Li, Qingning; Rao, Guanghui
Abstract: The piezoelectric responses were fluctuated with rising temperature for most of piezoceramics, which could affect the precision of service equipment directly. However, very few reports about improving stability of high temperature piezoelectric properties could be found out. In this work, the stability of high temperature piezoelectric properties for 0.7BFO-0.3BT ceramics was improved, which could be realized by suppressing relaxor phase transition. The ferroelectric-relaxor transition around 200 °C in 0.7BFO-0.3BT ceramics has an accelerating effect to depolarization process, which was inhibited by doping CuO, Li2 CO3 and ZnO. The frequency dependency of permittivity was decreased in the temperature range of 150–350 °C after doping, and the degradation of piezoelectric properties was suppressed. Contrary to above mentioned doping ceramics, fluctuant high temperature piezoelectric properties because of the aggravated relaxor phase transition expressed after doping MnO2 . As a result, the doped 0.7BFO-0.3BT ceramics with excellent electrical properties and improved stability of high temperature piezoelectric properties from room temperature to Curie temperature were obtained. The method for improving stability of high temperature piezoelectric properties opened a new window for extending the application range of high temperature piezoceramics. Highlights: Ferroelectric-relaxor transition has an accelerating effect to depolarization process. The in-time piezoelectric response and depolarization behaviors were studied by in-situ process. The high-temperature stability of piezoelectric properties was improved by suppressing ferroelectric-relaxor transition.